Perspectives in translational research in life sciences and biomedicine : translational outcomes research in life sciences and translational medicine. Volume 2 - Banerjee, Ena Ray (Springer, 2017)
This book is a collation of translational research outcomes in the area of life research, which was formerly used mainly for academic pursuits. The studies described focus on innovative interdisciplinary approaches to unraveling problems in life sciences and biomedicine using biodiversity exploration and green technology. The techniques and models presented offer a ready reckoner for researchers in academic institutions and industry, and also provide valuable insights into fundamental research. The book discusses topics such as tissue engineering to create lineage-specific cells for tissue-specific regeneration; how combination cultures of commensalistic bacteria can help boost immunity; development of functional food from natural products from plant, animal, and microbial sources in the nutraceuticals domain; as well as synthesis and mechanisms in nanomedicine and nanoscaffolds in biomedicine. The studies and discourses described touch upon topics that explore biodiversity for the development of disease models, toxicity studies, developmental studies, and harvesting of bioactive compounds for alternative income generation and poverty alleviation, and as a result, bring about economic and ecologic sustainability. This multidimensional and multidisciplinary book focuses on tissue-specific targeting by nanodrugs, development of bioengineering formats for cell- based, nutraceutical-based, functional-food-based and antibody-based green therapy designed tackle multifaceted diseases and syndromes.